Strategi Collaborative Governance dalam Peningkatan Pendapatan Asli Daerah (Studi pada BPKPD Kota Banjar) - Asep Mulyana (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is motivated by the still not maximal local revenue in the city of Banjar. This is indicated by the low quality of human resources, lack of socialization, low innovation, weak level of supervision and low stakeholder support from various parties in collaborating. Research is focused on studies using the theoretical approach of Emerson, Nabatchi & Balogh (2011), namely the Collaborative Governance Regime (CGR) model through 1). System context dimension 2). Drivers dimensions include (leadership, incentive consequences and interdependence), and 3). The dynamics of collaboration (Principled Engagement, shared motivation, and capacity for joint action). With the aim of the research to examine and analyze the implementation and the constraints that have caused it to be ineffective, as well as an effective strategy for implementing collaborative governance in increasing Regional Original Income in the City of Banjar. The research method uses descriptive analysis with a qualitative research approach. Data collection techniques through interviews, literature studies and observation. The research results show: 1). The implementation of collaborative governance in increasing Local Own Revenue in the City of Banjar on the dynamics dimension of collaboration can be said to have not run optimally, more concrete efforts are still needed related to motivation, awareness, work systems and technical policy support while on the system context and drivers dimensions concerning the availability of resources resources, and budget constraints as well as the level of supervision has been carried out optimally. 2). Obstacle factors in the implementation of collaborative governance in increasing Local Revenue in the City of Banjar, namely the low level of communication and coordination; lack of human resources and budget, lack of technical regulatory support regarding the involvement of stakeholders (private parties and community leaders); as well as the low support and commitment of policy makers from members of the legislature, regional tax-producing apparatus organizations, and stakeholders (private parties and community leaders). 3). Collaborative governance strategies in increasing effective Regional Original Revenue (PAD) in Banjar City are aggressive growth strategies by maintaining the previous strategy and optimizing the strengthening of the second availability of human resources, budget and infrastructure; maximizing the clarity of Standard Operating Procedures (SOP), regarding tax collection, support from the private sector and other OPDs, as well as optimizing the involvement of cross-sectoral collaboration (government, private parties and community leaders) through Collaborative Governance in the City of Banjar.